Does Burnout Affect Academic Achievement? A Meta-Analysis of over 100,000 Students - Madigan, Daniel J.; Curran, Thomas (Educational psychology review, 2021)
Burnout is understood to have many adverse consequences for students. However, several equivocal findings in the literature mean that it is currently unclear to what extent burnout affects academic achievement. To address this lack of clarity, the aim of the present study was to provide a first meta-analysis of the relationship between burnout and academic achievement. A literature search returned 29 studies (N = 109,396) and 89 effect sizes. Robust variance meta-analyses indicated that total burnout had a significant negative relationship with academic achievement (r c ⁺ = – .24). A similar pattern of relationships was found for each of the three symptoms of burnout (exhaustion [r c ⁺ = – .15], cynicism [r c ⁺ = – .24], and reduced efficacy [r c ⁺ = – .39]). There was some evidence that the instrument used to measure burnout moderated the relationship between reduced efficacy and achievement. Taken together, the findings suggest that burnout leads to worse academic achievement in school, college, and university.